THE INFLUENCE OF PARENTING PATTERNS OF PARENTS AND PEERS ON LEARNING DISCIPILINE OF VOCATIONAL HIGH SCHOOL STUDENTS IN EAST JAKARTA - Kurniasari, Harini Dwi; Susanti, Santi; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The study aims to determine the infulence of parenting style and peers to the learning dicipline. The method used is a quantitative method. The research population reached 185 SMK students majoring in Accounting in East Jakarta. The sample used was 126 students using proportional random sampling technique. Data collection using a questionnaire instrument with a Likert scale. The data analysis technique used is descriptive statistical analysis, multiple regression equations, test requirements analysis, hypothesis testing and determination test. The results of data analysis show that the data used are normally distributed and linear. The coefficient of determination test results show that the percentage of parenting styles and peers to explain the learning discipline variable simultaneously is 33.9%. Simultaneously, the results showed that there was a significant influence between parenting styles and peers on learning discipline. Partially, there is a positive and significant influence between parenting styles on learning discipline, there is also a positive and significant influence between peers on learning discipline.